2019
DOI: 10.1016/j.socscimed.2018.12.020
|View full text |Cite
|
Sign up to set email alerts
|

“You don't trust a government vaccine”: Narratives of institutional trust and influenza vaccination among African American and white adults

Abstract: Vaccine confidence depends on trust in vaccines as products and trust in the system that produces them. In the US, this system consists of a complex network connecting pharmaceutical companies, government agencies, and the healthcare system. We explore narratives from White and African American adults describing their trust in these institutions, with a focus on influenza vaccine. Our data were collected between 2012 and 2014 as part of a mixed-methods investigation of racial disparities in influenza immunizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
217
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(234 citation statements)
references
References 34 publications
13
217
3
1
Order By: Relevance
“…These findings challenge and extend previous findings on the role of trust in determining health attitudes and behaviors. Namely, extant research examining trust has identified mistrust in government as a critical barrier to positive health attitudes and behaviors (Jamison et al, 2019;Larson et al, 2018;Whetten et al, 2006). In contrast, our findings suggest that trust in governmental leadership can be a hindrance to health literacy when the messages issued by governmental leaders are at odds with those from public health organizations and emerging evidence-based practices.…”
Section: Trust In Institutionsmentioning
confidence: 56%
“…These findings challenge and extend previous findings on the role of trust in determining health attitudes and behaviors. Namely, extant research examining trust has identified mistrust in government as a critical barrier to positive health attitudes and behaviors (Jamison et al, 2019;Larson et al, 2018;Whetten et al, 2006). In contrast, our findings suggest that trust in governmental leadership can be a hindrance to health literacy when the messages issued by governmental leaders are at odds with those from public health organizations and emerging evidence-based practices.…”
Section: Trust In Institutionsmentioning
confidence: 56%
“…However, it is difficult to interpret the differences in perceived risk, given that they are quite high in general, and so non-Hispanic Blacks’ lower perceived risk may be more realistic. Nonetheless, it is important to consider that minority groups may have less trust in governmental institutions as a result of longstanding structural racism [ 40 , 41 ]. Accordingly, governmental health promotions should focus on addressing higher risk of severe infection and morality in historically marginalized communities [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Together, our data further support low vaccination rates in non-Hispanic black women compared with high vaccination rates in Hispanic and non-Hispanic other race women. We speculate that communitylevel factors, such as the circulation of myths surrounding the influenza vaccine, social norms, and the level of trust in medical recommendations, may influence the differential uptake of antenatal influenza vaccine in these racial and ethnic groups [17,18].…”
Section: Discussionmentioning
confidence: 99%